Slack Resources and Corporate Social Responsibility Link: Evidence from Manufacturing Firms in Nigeria - Nnachi Egwu Onuoha; Nelson N. Nkwor (Journal of Accounting Auditing and Business, 2021)
Extant empirical literature indicates little or no study on the extent of corporate social responsibility (CSR), using evidence from Nigerian context, and mixed study findings regarding slack resources and CSR relationship. Accordingly, this paper explores the extent of CSR activities by manufacturing firms in Nigeria and the effects of absorbed and unabsorbed slack resources on CSR. Using data set collected through content analysis of the 2017 and 2018 annual reports of 12 manufacturing firms in Nigeria and analyzing same by conducting one sample Wilcoxon signed rank test and regression analysis, we find that whereas the extent of CSR activities by the studied firms is low and insignificant, absorbed and unabsorbed slack resources have significant positive effects on CSR activities. These findings serve as a robust empirical basis for policy makers to insist on improved level of CSR activities by manufacturing firms in Nigeria, and for managers and regulators to understand the importance of slack organizational resources in CSR investment decision making.